Tilted bi‐sense circularly‐polarized antenna and its application for radio frequency identification system. Issue 7 (24th February 2020) - Zhang, Wen‐Hai; Tam, Kam‐Weng; Lu, Wen‐Jun; Cheong, Pedro; Choi, Wai‐Wa; Ho, Sut‐Kam
Abstract: A tilted bi‐sense circularly polarized (CP) antenna and its application for UHF radio frequency identification (RFID) system is proposed. A planar concial monopole working as the electric dipole is designed at first. When a shorting pin is added, a loop radiator would be generated, and thus a pair of orthogonally oriented complementary dipoles is realized. In this way, both right‐handed circularly polarized (RHCP) and left‐handed circularly polarized waves (LHCP) are generated simultaneously in tilted directions within one hemisphere. Then, closed‐form formulas are derived to reveal the tunability mechanism of bi‐sense property and provide a design guideline for system application. It is demonstrated that flare angle of conical monopole has a linear relationship and sine function to CP beam direction and 3‐dB axial ratio (AR) beamwidth, respectively. Finally, antenna prototypes are fabricated and tested for validation. It is also demonstrated that at the tilted direction of θ = ± 45°, a 3‐dB AR bandwidth of 4.9%, and gain up to 5 dB are realized. Comparing with conventional microstrip patch antenna, an enhanced reading range over 5 m can be obtained in the tilted range from 40° to 75° and − 75° to −40° in UHF RFID sytem application.